Optimization of enzymatic interesterification of coconut (Cocos nucifera) and sesame (Sesamum indicum) oils using Thermomyces lanuginosus lipase by response surface methodology - Sivakanthan, S.; Madhujith, T. (Tropical Agricultural Research, 2017)
Blends of coconut (Cocos nucifera) oil (CO) and sesame (Sesamum indicum) oil (SO) were enzymatically interesrerified using aqueous lipase derived from Thermomyces lanuginosus and the reaction conditions were optimized using Response Surface Methodology (RSM). A three-factor, three-level central composite design (face centred cube design) was employed to optimize the reaction parameters, namely temperature (45-65 °C), time (16-48 h) and mass ratio of oils (CO:SO; 70:30 - 50:50). Lipase, diluted in phosphate buffer (pH 8) was used at 0.2% (v/w) of the substrate. Degree of interesterification (DI), and the ratio of monounsaturated and polyunsaturated fatty acids (MUFA:PUFA) of triacylglycerols (TAGs)were used as response variables. Triacylglycerol (TAG) fractions of the samples were separated using Thin Layer Chromatography (TLC) and the fatty acid composition of TAGs was determined using Gas-Liquid Chromatography (GLC). The linear and squared effects of temperature and time were significant (p <0.05) for DI while the reaction conditions did not exhibit a significant (p<0.05) effect on MUFA:PUFA ratio. The optimum conditions for enzymatic interesterificationwere45 °C (temperature), 40.24 h (time) and 70:30 (weight ratio of CO:SO).Under these optimized conditions, the DI was 28.98% and MUFA:PUFA was 1.50±0.06. According to the response surface regression analysis, the R2 value for DI versus reaction parameters was 91.85% and MUFA:PUFA ratio versus reaction parameters was 61.82%. Therefore it can be concluded that enzymatic interesterification can effectively be applied to develop nutritionally and functionally superior modified oilknown as structured lipids using coconut and sesame oils.
Keywords: Coconut oil; interesterification; lipase; optimization; sesame oil